Maerid amphipods (Crustacea: Amphipoda) from Okinawa, Japan with description of a new species - Sir, Sally; White, Kristine N. (Zootaxa, 2022)
Two species of Maeridae are reported from extensive tidal flat collections on the east coast of Okinawa Island, Japan. A range extension is reported for Ceradocus mizani Lim, Azman & Othman, 2010. Elasmopus mukuinu sp. nov. is described and is most similar to species in the Elasmopus pectenicrus (Bate, 1862) group in Hughes & Lowry (2011). The new species is distinguished from other species based on the gnathopod 2 propodus bearing a subrectangular hump near insertion of the dactylus, the propodus being covered in dense tufts of long setae and the posterior margins of pereopods 5, 6, and 7 (almost smooth, serrate, and crenulate, respectively).